Gothic ivories Calouste Gulbenkian Collection - Guérin, Sarah M. (Scala, 2015)
The Calouste Gulbenkian Museum in Lisbon holds a remarkable set of gothic ivories, including rare pieces of exceptional quality. This fully illustrated book brings these exquisite pieces to a wider audience, appealing not only to specialists but also to the general reader. Lavish colour reproductions of the ivories, accompanied by an expert text and contextual images from other collections, make this an accessible guide to this fascinating subject